Dormancy overcoming in catanduva (Piptadenia moniliformis Benth.) seeds - Benedito, Clarisse (2008)
The experimental was carried out at the Seed Analysis Laboratory of the Crop Science Department, Universidade Fedral Rural do Semi-Árido (DCV/UFERSA) in order to obtain the efficient method for overcome dormancy of catanduva (Piptadenia moniliformis Benth.) seeds. Seeds had been harvested of trees in the Mossoró County, RN, Brazil. The treatments were: immersion in hot water (100 ºC) for 5; 10; 15 and 20 minutes; immersion in sulphuric acid - pa for 5; 10; 15 and 20 minutes; mechanic scarification with water sandpaper and control. Seeds had been placed to germinate at 20-30 ºC temperature in the sand substratum. It was considered the following parameters: germination percentage, hard seed percentage, deceased seed percentage, speed of emergence index and abnormal seedlings at 20 days after sowing. The experimental design was completely randomized with four replications of 50 seeds each one. The treatments of immersion in sulphuric acid (95%) for 10 and 15 minutes and hot water (100 ºC) for 10 e 15 minutes showed promising results for overcome dormancy of catanduva seeds.